The Concept Of Sharia Accounting In Nahusanamang Custom In Tulehu Village - Tuasalamony, Ardhiatul Halima; Sudirman, Sitti Rahma; Usman, Usman; Rezkiyanti, Nur Alfiah; Samual, Nurul Rahima (INVOICE : JURNAL ILMU AKUNTANSI, 2024)
The primary objective of this study is to explore the application of Islamic accounting principles within the context of the nahusanamang custom. Employing qualitative methods with a phenomenological approach, the research delves into the interpretation of Islamic accounting concepts within nahusanamang. Through this investigation, several key elements emerge, shedding light on the significance of nahusanamang within Islamic accounting frameworks. Nahusanamang, within the purview of Islamic accounting, encompasses various facets including assets, liabilities, temporary shirkah funds, equity, receipts and expenses (encompassing profits and losses), cash flow, zakat funds, and benevolent funds. These interpretations are deeply rooted in the traditions prevalent within the community, illustrating the integration of Sharia principles into the accounting practices associated with nahusanamang. The traditional understanding of nahusanamang within Islamic accounting underscores its broader role beyond mere financial transactions. It embodies religious values, fostering familial and social bonds while alleviating the burdens of individuals with pressing needs, known as sahibul hajat. This research underscores the significance of incorporating Islamic principles into accounting practices, emphasizing the broader societal and ethical dimensions inherent in financial transactions. By contextualizing nahusanamang within Islamic accounting frameworks, this study contributes to a deeper understanding of how religious values intersect with financial management practices within specific cultural contexts. Ultimately, the findings of this study provide valuable insights for practitioners and scholars alike, highlighting the importance of aligning accounting practices with religious and cultural values to ensure ethical and socially responsible financial management within diverse communities.